ROLE AND POSITION OF STUDENTS IN THE OPERATION OF PHYSICAL EDUCATION IN SMA CITY SEMARANG - Yulianingsih, Ika (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2022)
This research uses descriptive quantitative method. The population of this research is 54 private high schools in Semarang City which occupy 8 bottom ranks based on the results of the 2013/2014 UAN score The sampling technique based on purposive sampling consisted of the 8 lowest private high schools in Semarang City. The research instrument used a questionnaire and interview. The data analysis technique used percentages and continued with the Quantitative Index Index coefficient (IQV). The results of the study of students 'understanding of PE in terms of the analysis of 3 ideators the average results in the good category, the role of students in PE learning planning in terms of 5 indicators have the average results in good categories, students' perception of the implementation of PJOK subjects in terms of 4 indicators with average results that have a good category.